Establishment and application of a dual RPA-LFD rapid detection method for Salmonella Pullorum and Salmonella Enteritidis - Can Wang; Tingting Zeng; Houxun Ya; Lijun Wan; Ming Yan; Sisi Luo; Meng Li; Yanfei Deng; Hongyu Ren; Zuoxin Chen; Zhixun Xie; Liji Xie (PLoS ONE, 2025)
Salmonella species are known to cause a significant decline in poultry production performance and to contaminate various stages of the breeding process, with Salmonella Pullorum ( S . Pullorum) and Salmonella Enteritidis ( S . Enteritidis) being the predominant serotypes responsible for infection in poultry. For rapid diagnosis at an early stage, we developed a method involving dual recombinase polymerase amplification (RPA) combined with a lateral flow dipstick (LFD) in this study, and primers were designed to target the traJ gene of S . Pullorum and the Sdf Ⅰ gene of S . Enteritidis. The primers and probes were screened, and the reaction conditions were optimized. The results showed that dual RPA successfully amplified S . Pullorum and S . Enteritidis DNA within 15 min at 37°C, and when combined with LFD, the entire process (amplification and detection) was completed within 20 min. The detection limits for S . Pullorum and S . Enteritidis were 1.56 × 10 2 CFU/mL and 1.38 × 10 2 CFU/mL, respectively. The developed dual RPA-LFD method specifically targets S . Pullorum and S . Enteritidis and exhibits no cross-reactivity with other common pathogenic microorganisms. The results for the clinical samples were fully consistent with those obtained using the Bacteriological Analytical Manual (BAM) method. The results of this study demonstrated that the developed dual RPA-LFD method is simple, rapid, specific, and highly sensitive for the simultaneous visual detection of S . Pullorum and S . Enteritidis, providing a technical reference for primary veterinary laboratories and veterinary field tests.